Perspective of low-cost biosensors for genotoxic potential evaluation of urban air. (30th September 2020) - Traversi, D; Pignata, C; Anedda, E; Gilli, G
Abstract: Background: Biosensor technology can potentially revolutionise the area of air pollution monitoring by providing data on early biological effect induction. Such data can be developed for supplementing routine pollution monitoring, improving exposure estimation, including a potential effect estimation and raising community awareness about air pollution. Especially in consideration of complex biological effect such as mutagenic, genotoxic and other proved effects due to the air mixture exposure. The aim of the study is to propose a short-time biosensor for the mutagenic properties evaluation of air pollution. Methods: A simple biosensor was developed using genetically modified microorganisms. A first sampling session was conducted in one of the most air-polluted city of Italy using the biosensor and collecting the data of the usual monitoring system, including PM2.5, PM10, NOx, PAHs and metals concentrations. Results: The biosensor is able to answer to polluted air mixture indicating a valuable genotoxic effect. Such effect - expressed in relation to the air sampled volume - is comparable to that recorded by traditional genotoxicity in vitro assay on organic extract of particulate matter. Moreover, a comparison with reference measurements is conducted. Repeatability, reproducibility, stability, limit of detection as the impact of environmental factors on biosensor output have been discussed. Conclusions: Due to copious difficulties arising when airborne emissions are sampled, biological assays have been applied only sporadically. Aerosol particles are generally collected on a filter and following extraction procedure and bioassay were performed. Monitoring using the biosensor require low sample quantity, directly colliding with the microorganism, and supply good choice when air genotoxicity are to be determined. Key messages: Low-cost biosensors can empower high density monitoring of air pollution. The proposed biosensor is able to evaluate genotoxic properties of the air mixture even if data quality is a major concern for its employment.